The Correlation between Arabic Learning Motivation and Arabic Language Competence of Education Study Program Students in Post- COVID-19 Pandemic - Hidayah, Nurul; Mukmin, Mukmin; Marfuah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2023)
The COVID-19 pandemic has had a major impact on learning, especially student learning motivation, which also has an impact on the Arabic language competence of high school students when they turn into university students. Students are not only required to be able to learn independently but also have to answer the challenges of the 21st century, especially to communicate using Arabic. The purpose of this article is to explore university students' motivation in learning Arabic after online learning and its correlation with their Arabic language competence. A quantitative approach was used with a bivariate correlation research method. The population of this study was students at UIN Raden Fatah Palembang with a sample of 1213 people with diverse scientific specifications. The research analysis was conducted with prerequisite test followed by correlation test and univariate test. The results showed that the motivation to learn Arabic language of students of Arabic language education study program has a positive and significant correlation with the level of Arabic language competence despite having gone through online learning for several years when students are in secondary education. Therefore, it is important for Arabic teachers to continue to innovate in learning by using digital learning media to increase motivation in Arabic. Learning should also be based on digital literacy, so that students can become agents of change by breaking the shackles of the lack of infrastructure in schools and replacing them with media that are ready to access and fill content related to Arabic language learning.